Political Rights of Former Prisoners in Electoral Democracy: A Contextualized Islamic Political Perspective from Indonesia and Uzbekistan - Shulhan Iqbal Nasution; Sugih Ayu Pratitis; Mhd Ansor Lubis; Windy Sri Wahyuni; Bazarova Dildora Baxadirovna (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The restriction of passive political rights for former prisoners represents a globally contested legal phenomenon at the intersection of democratic integrity, human rights, and moral leadership standards. Despite its prevalence, comparative normative scholarship examining this restriction through an integrated Islamic political jurisprudence framework remains limited. This study addresses that gap by analyzing the legal dynamics of electoral democracy and the restriction of passive political rights for former convicts through a comparative study of Indonesia and Uzbekistan, integrated with a Siyāsah Shar'iyyah perspective. Employing normative legal research with statutory, conceptual, and comparative approaches, this study systematically examines constitutional frameworks, constitutional court rulings, and electoral reform legislation in both jurisdictions. The findings reveal three convergent dimensions: first, both countries ground political right restrictions in the principles of proportionality, legal certainty, and public interest protection, though through contrasting institutional mechanisms — Indonesia through judicialized constitutional review and Uzbekistan through state-led administrative reform; second, Indonesia's Constitutional Court Decision No. 56/PUU-XVII/2019 establishes a mandatory five-year post-sentence waiting period as a sociological rehabilitation filter, while Uzbekistan's 2019 Electoral Code liberalized voting access without fully resolving the passive rights gap for serious offenders; third, from a Siyāsah Shar'iyyah standpoint, leadership eligibility is conditioned upon Adalah (moral integrity) and Amanah (trustworthiness), wherein criminal conviction — particularly for corruption — constitutes a temporary forfeiture of Adalah, recoverable through verified Tawbah (repentance) and Raddul I'tibār (rehabilitation), yet legitimately subject to conditional restriction under Maṣlaḥah Mursalah (public interest). This study contributes a normative-comparative model demonstrating that temporal restrictions on the right to be elected are compatible with both international human rights standards and Islamic political ethics, provided they are proportional, non-discriminatory, and legally bounded. The findings offer policy implications for Muslim-majority democracies seeking to harmonize electoral integrity with rehabilitative justice frameworks.